Role of non-invasive imaging in the management of coronary artery disease: an assessment of likely change over the next 10 years. A report from the British Cardiovascular Society Working Group. Issue 4 (30th March 2007) - Gershlick, A H; de Belder, M; Chambers, J; Hackett, D; Keal, R; Kelion, A; Neubauer, S; Pennell, D J; Rothman, M; Signy, M; Wilde, P
Abstract : Coronary angiography has been the gold standard for determining the severity, extent and prognosis of coronary atheromatous disease for the past 15–20 years. However, established non-invasive testing (such as myocardial perfusion scintigraphy and stress echocardiography) and newer imaging modalities (multi-detector x ray computed tomography and cardiovascular magnetic resonance) now need to be considered increasingly as a challenge to coronary angiography in contemporary practice. An important consideration is the degree to which appropriate use of such techniques impacts on the need for coronary angiography over the next 10–15 years. This review aims to determine the role of the various investigation techniques in the management of coronary artery disease and their resource implications, and should help determine future service provision, accepting that we are in a period of significant technological change.